Antibacterial Prodrugs to Overcome Bacterial Antimicrobial Resistance - Catarina Maria; Ana M. de Matos; Amélia P. Rauter (MDPI AG, 2024)
Antimicrobial resistance (AMR) is an increasingly concerning phenomenon that requires urgent attention because it poses a threat to human and animal health. Bacteria undergo continuous evolution, acquiring novel resistance mechanisms in addition to their intrinsic ones. Multidrug-resistant and extensively drug-resistant bacterial strains are rapidly emerging, and it is expected that bacterial AMR will claim the lives of 10 million people annually by 2050. Consequently, the urgent need for the development of new therapeutic agents with new modes of action is evident. The antibacterial prodrug approach, a strategy that includes drug repurposing and derivatization, integration of nanotechnology, and exploration of natural products, is highlighted in this review. Thus, this publication aims at compiling the most pertinent research in the field, spanning from 2021 to 2023, offering the reader a comprehensive insight into the AMR phenomenon and new strategies to overcome it.